PENGARUH PENAMBAHAN PLASTIK BEKAS TIPE POLYETHYLENE TEREPHTHALATE (PET) TERHADAP DAYA LEKAT CAMPURAN LASTON LAPIS AC-WC - Debataraja, Semangat Marudut Tua; Sihite, Natalius (Prodi Teknik Sipil Fakultas Teknik Universitas Darma Agung, 2023)
The problem in this research is the increasing amount of plastic waste that is difficult to decompose creates an idea for me to use as one of the additives or mixtures in making asphalt mixtures. The types of plastic waste that are mostly found are drink bottles and plastic bags. This type of plastic can only be recycled only once with the name PET (Polyethylene Terephthalate). The addition of plastic to the asphalt mixture aims to optimize the characteristics of the AC-WC smooth asphalt mixture and reduce the amount of waste. Plastic mixing is carried out by means of a dry method whose plastic content is 5%, 10% 15% and 30% of the weight of optimum asphalt content. From the Marshall test conducted with the addition of PET plastic waste, the Stability value at 5% was 2005,967 kg, compared to the absence of additional plastic waste with a record number of 1961,534 kg. Density value with the addition of plastic at 5% level was 2.355% decreased compared to the elimination of the addition of this plastic mixture with a value of 2.359%. The value of Flow with the addition of plastic at a 5% level of 3,200% has increased compared to without the addition of plastic with a value of 3,100%. The value of VIM with the addition of plastic at a level of 5% is 4.453% compared without the addition of this element from the plastic waste that is difficult to decompose with a value of 4.297%. VFA value with the addition of plastics at 5% level was 73.493% decreased compared to no plastic additions amounting to 74.216%. The VMA value with the addition of plastic at 5% level was 16,801%, an increase compared to without the addition of plastic with a magnitude of 16,665%. MQ value with the addition of plastic at 5% content of 626,865 kg / mm has decreased compared to without the addition of plastic 632,753 kg / mm.